Wpływ pandemii COVID-19 na cyfryzację administracji publicznej - Bednarski, Paweł (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2023)
The application of security measures in order to prevent the spread of the SARSCoV-2 virus epidemic adversely affected the implementation of citizenship rights. The limitation of access to offices has become an incentive to accelerate the digitisation of public administration and objectively positive achievements in the implementation of public administration e-services, education and health care systems. Without denying the successes in the implementation of information and communication technologies, it is also necessary to point out the disadvantages and negative effects of the actions taken.
Keywords: pandemic; digitisation; public administration